Eksistensi bisnis kuliner halal melalui digital marketing di era new normal - Fita Nurotul Faizah (SERAMBI: Jurnal Ekonomi Manajemen dan Bisnis Islam, 2022)
This study aims to analyze the existence of the halal culinary business through digital marketing in the new normal era. The method used is descriptive qualitative. The results show that the halal culinary business in the new normal era still exists. This is supported by the application of digital marketing, especially during the COVID-19 pandemic and business opportunities in the form of the majority of the Indonesian population being Muslim, increasing demand for halal food, business digitization, lifestyle, easy halal certification, product diversity, local wisdom, efficiency and effectiveness as well as the development of e-commerce. However, the challenges faced are in the form of business sustainability, other cheaper halal products, variety of products from large industries, ease of entering the market and the emergence of similar new businesses. For this reason, alternative strategies include utilizing social media by displaying complete information regarding shops or stalls and products, displaying clear and attractive images, establishing good communication with customers, offering promos or discounts, paying attention to customer reviews and correcting any mistakes and being active on social media.